Understanding the Link Between Organizational Communication and Innovation: An Examination of Public, Nonprofit, and For-Profit Organizations in South Korea. (June 2018) - Suh, Jiwon; Harrington, James; Goodman, Doug
Innovation and internal communication are essential for any successful organization. Although communication within organizations has long been studied in the for-profit sector, we still know little about the impact of communication types on innovation in the public and nonprofit sectors. To examine this question, we leverage and construct a longitudinal dataset using 5 years of the Korean Workplace Panel Survey (KWPS) from 2005 to 2013. Employing media richness theory, this study finds that internal communication positively influences innovation in the for-profit sector, which is a finding consistent with prior studies. Similarly, in the nonprofit sector, we find that meeting with the executive director and the number of communication channels utilized in an organization has a positive impact on innovation. However, we do not find that these communications have any impact in the public sector.